Collagen hydroxylysine glycosylation: non-conventional substrates for atypical glycosyltransferase enzymes. (30th April 2021) - De Giorgi, Francesca; Fumagalli, Marco; Scietti, Luigi; Forneris, Federico
Abstract : Collagen is a major constituent of the extracellular matrix (ECM) that confers fundamental mechanical properties to tissues. To allow proper folding in triple-helices and organization in quaternary super-structures, collagen molecules require essential post-translational modifications (PTMs), including hydroxylation of proline and lysine residues, and subsequent attachment of glycan moieties (galactose and glucose) to specific hydroxylysine residues on procollagen alpha chains. The resulting galactosyl-hydroxylysine (Gal-Hyl) and less abundant glucosyl-galactosyl-hydroxylysine (Glc-Gal-Hyl) are amongst the simplest glycosylation patterns found in nature and are essential for collagen and ECM homeostasis. These collagen PTMs depend on the activity of specialized glycosyltransferase enzymes. Although their biochemical reactions have been widely studied, several key biological questions about the possible functions of these essential PTMs are still missing. In addition, the lack of three-dimensional structures of collagen glycosyltransferase enzymes hinders our understanding of the catalytic mechanisms producing this modification, as well as the impact of genetic mutations causing severe connective tissue pathologies. In this mini-review, we summarize the current knowledge on the biochemical features of the enzymes involved in the production of collagen glycosylations and the current state-of-the-art methods for the identification and characterization of this important PTM.